Designation of certain filamentous fungal genes identified by molecular cloning. - S. J. Gurr; J. R. Kinghorn (Fungal Genetics Reports, 1988)
In a recent review entitled "The structure and organization of nuclear genes of filamentous fungi" (Gurr et al., 1987) we gave conventional designations to certain hitherto undesignated genes of filamentous fungi.